Penanaman Karakter Siswa Melalui Ragam Bahasa dalam Kegiatan Pembelajaran Bahasa Indonesia - Ahmad Bahtiar; Mahsusi Mahsusi; Nuryani Nuryani (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2021)
[STUDENT CHARACTER BUILDING THROUGH VARIOUS LANGUAGES ​​IN INDONESIAN LANGUAGE LEARNING ACTIVITIES]. This study aims to describe character planting through the variety of languages used in Indonesian language and literature learning activities in schools. Learning activities are activities that are dominated by the delivery of material by the teacher. In delivering the material, the teacher uses a variety of languages. Therefore, the use of various languages can also be used as a way to instill student character. The research method used in this research is descriptive qualitative. The location of this research is Triguna Utama Senior High School with the research subjects of class XA on Indonesian Language and Literature learning. The method of data collection was carried out by direct observation in learning activities and in-depth interviews with students and teachers as well as several parties involved in learning activities. Based on the analysis carried out, it can be concluded that in learning activities, the use of formal (formal), consultative, relaxed, and familiar modes are found. The use of various languages by the teacher is able to create various situations and contexts that take place in learning. The variety of languages used can also be used to instill student character both in the classroom environment and outside the classroom. When the teacher uses language with a polite choice of words, students will also follow. Likewise in other contexts when the teacher chooses to use a variety of familiar languages, students will also follow the familiar language choice.